PENGARUH PENDEKATAN WHOLE LANGUAGE TERHADAP KEMAMPUAN MEMBACA PERMULAAN USIA 5-6 TAHUN TK MAWAR KHATULISTIWA - Maulidia, Citra Rizki; Fadillah, Fadillah; Miranda, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the effect of the whole language approach on the ability to read the beginning of children aged 5-6 years in TK Mawar Khatulistiwa. This study uses quantitative methods, the form used is a real experiment.  The design used was the pretest-posttest group design. The sample in this study were all children aged 5-6 years in TK Mawar Khatulistiwa. Data collection methods used are observation, documentation and field notes. The technique used to analyze the data is descriptive analysis. The results of this data analisys compare between experimental and control groups. The results of the study show that value of  is 2,148. While the value of with a level of 5% for one side and 0,025 for two sides with degrees of freedom (db) 26 then obtained 2,056. Because the value 2,148 2,056), then H0 is rejected. That is to say, there is an influence of the whole language approach on the ability to read the beginnings of children aged 5-6 years at TK Mawar Khatulistiwa. Calculated using the formula of the coefficient of determination equal to 81,90% the influence of the whole language approach to the ability to read the beginning of the child ad TK Mawar Khatulistiwa. The conclusion is the whole language approach affects the ability to read the beginning of the child.Keywords: Approach, Reading Ability, Whole Language.